Theoretical Re-formulation of the Clinical Method: The Therapeutic Clinical Diagnostic Method - Luis Alberto Corona Martínez (Medisur)
This article shows a theoretical model of the solution state or tretament of the medical attention process as a complementary phase of diganosis of the mentioned process.the development of this stage has been carried out according to the medical assistance conception as a taken decisions process and which is formed by the following elements, 1) Development of solution options, 2) Evaluation, selection, and application of options, 3) Evaluation of taken solutions. Diferences between behaviour options and therapeutic management are established, and the importance of using diverse factors to give individuality to the process is reinforced. Some limitations of this elaborated model is also shown.